2011
DOI: 10.1063/1.3551709
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and transport properties of a nanometer-scale Au/AlN(0001)/Au junction from first-principles

Abstract: A nanometer-scale Au/Al(0001)/Au junction has been studied by first-principles calculation methods. The calculated current density-voltage curve shows Ohmic behavior, switching effect, and negative differential conductance in various bias ranges. The electronic structure shows the existence of an intrinsic band tilt due to the polar nature of the AlN film, which gives rise to the presence of hole states at the N-surface side and interface states at the Al-surface side of the AlN film. The bias induced changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Finally, recent experimental and theoretical studies have shown the importance of the transition‐metal adsorption on AlN surfaces; in particular, has been studied the V , Ti , Cr , Au adsorption on AlN surfaces. Additionally, it also has been studied the formation of transition‐metal interlayers on the AlN(0001) surface, as: VN , TiN , CrN , NbN and ZrN .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent experimental and theoretical studies have shown the importance of the transition‐metal adsorption on AlN surfaces; in particular, has been studied the V , Ti , Cr , Au adsorption on AlN surfaces. Additionally, it also has been studied the formation of transition‐metal interlayers on the AlN(0001) surface, as: VN , TiN , CrN , NbN and ZrN .…”
Section: Introductionmentioning
confidence: 99%